Optimal Joint Allocation of MultiSlot Spectrum Sensing and Transfer Power in MultiChannel Cognitive Radio. (20th August 2014) - Liu, Xin; Jia, Min; Gu, Xuemai; Kong, Fanqiang; Jing, Qingfeng
Abstract : In multichannel, cognitive radio (CR), the secondary user (SU) is allowed to utilize multiple subaltern frequency bands of the primary user (PU), when these bands, namely, subchannels are not currently being used. To support this spectrum reuse functionality, the SU is required to sense each subchannel, and only the subchannels wherein the PU is inactive are available for the spectrum access of the SU. In this paper, a multislot spectrum sensing and transfer scheme for multichannel CR is proposed, whose sensing stage is divided into several time slots allocated to the subchannels for spectrum sensing. While guaranteeing the spectrum sensing performance on each subchannel and limiting the interference to the PU, we formulate an optimization problem that maximizes the SU's aggregate throughput by jointly allocating the optimal number of sensing time slots and the optimal transfer power to each subchannel. Theoretical analysis is given to prove the feasibility of the proposed optimization problem and simulation results are presented to show the notable improvement on the SU's throughput when the sensing time slots and the transfer power are both optimized by the proposed scheme.